Spectrophotometric determination of erbium using kojic acid dye in different rare earth concentrates - A.A. Abdou; S.A. Abo-El-Enein; H.K. Fouad; N.A. Fattah; E.M. El Desouky (Egyptian Journal of Petroleum)
A sensitive and selective spectrophotometric method was studied for the determination of erbium (Er) with kojic acid dye (koj) and cetylpyridinium chloride (CPC) as a cationic surfactant from Egyptian monazite and xenotime concentrates using third derivative spectrophotometry. The calibration curve was linear from 1 to 150 µg/mL erbium. The influence of various parameters and reaction conditions for optimum complex formation were investigated. The relative standard deviation for determination of 1 µg/mL erbium was found to be 1.5 after 5 repeated determinations with percentage error for Er determination from monazite and xenotime concentrates 6.4% and 4.48% respectively. The molar absorptivity of conventional and third derivative spectrum were 0.14 × 103 M−1 cm−1 and 0.13 × 103 M−1 cm−1 respectively and the detection limit was 1 µg/mL. Keywords: Erbium, Kojic acid dye, Cetylpyridinium chloride, Egyptian monazite, Xenotime